FcγRIIb Exacerbates LPS-Induced Neuroinflammation by Binding with the Bridging Protein DAP12 and Promoting the Activation of PI3K/AKT Signaling Pathway in Microglia - Han Y; Wang L; Ye X; Gong X; Shao X (Dove Medical Press, 2024)
YingWen Han,* Luyao Wang,* Xiaokun Ye, Xue Gong, Xiaoyi Shao Department of Immunology, Medical School, Nantong University, Nantong, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyi Shao, Department of Immunology, Medical School, Nantong University, 19 Qixiu Road, Nantong, Jiangsu, 226001, People's Republic of China, Email xy_shao@163.comIntroduction: This paper focuses on the expression and role of FcγRIIb in neuroinflammation, exploring the molecular mechanisms by which FcγRIIb interacts with the bridging protein DAP12 to regulate the PI3K-AKT signaling pathway that promote neuroinflammation and aggravate neuronal injury.Methods: LPS-induced neuroinflammation models in vivo and in vitro were constructed to explore the role and mechanism of FcγRIIb in CNS inflammation. Subsequently, FcγRIIb was knocked down or overexpressed to observe the activation of BV2 cell and the effect on PI3K-AKT pathway. Then the PI3K-AKT pathway was blocked to observe its effect on cell activation and FcγRIIb expression. We analyzed the interaction between FcγRIIb and DAP12 by Immunoprecipitation technique. Then FcγRIIb was overexpressed while knocking down DAP12 to observe its effect on PI3K-AKT pathway. Finally, BV2 cell culture supernatant was co-cultured with neuronal cell HT22 to observe its effect on neuronal apoptosis and cell activity.Results: In vivo and in vitro, we found that FcγRIIb expression was significantly increased and activated the PI3K-AKT pathway. Contrary to the results of overexpression of FcγRIIb, knockdown of FcγRIIb resulted in a significant low level of relevant inflammatory factors and suppressed the PI3K-AKT pathway. Furthermore, LPS stimulation induced an interaction between FcγRIIb and DAP12. Knockdown of DAP12 suppressed inflammation and activation of the PI3K-AKT pathway in BV2 cells, and meantime overexpression of FcγRIIb suppressed the level of FcγRIIb-induced AKT phosphorylation. Additionally, knockdown of FcγRIIb inhibited microglia activation, which induced neuronal apoptosis.Discussion: Altogether, our experiments indicate that FcγRIIb interacts with DAP12 to promote microglia activation by activating the PI3K-AKT pathway while leading to neuronal apoptosis and exacerbating brain tissue injury, which may provide a new target for the treatment of inflammatory diseases in the central nervous system.Keywords: LPS-induced neuroinflammation, FcγRIIb, DAP12, microglia, PI3K-AKT